GAMIFICATION APPROACHES IN ELT: IMPLEMENTATION AND ITS INFLUENCE ON ESP ACCOUNTING STUDENTS' VOCABULARY MASTERY - Prasongko, Angga; Farikha, Ninik; Lestari, Pritantina Yuni; Hamida, Ulfi Dina (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
High motivation and interest in the teaching and learning process are important factors in achieving learning objectives. Lecturers in the classroom have a very important role in achieving these objectives. Lecturers must use a creative, innovative, and modern learning approach in order to achieve learning objectives. Research with the aim of providing a breakthrough as a role model for technology-based English teaching and learning activities in the context of English for Specific Purpose (ESP) needs to be applied to answer these problems. This research is a qualitative type with a descriptive approach supported by quantitative data through a quasi-experimental design. The research subjects implemented by the Word-wall game in learning were carried out by lecturers through five stages. The use of the Word-wall game in learning activities significantly increased students' English vocabulary scores. The results of the study showed that the Word-wall game is an effective and interesting learning media to improve students' English vocabulary mastery and has an effect on increasing student motivation and participation in class to learning process.